ASSESSMENT OF GENETIC PARAMETERS IN MAIZE (Zea mays L.) FOR YIELD AND ASSOCIATED TRAITS: ASSESSMENT OF GENETIC PARAMETERS IN MAIZE (Zea mays L.) FOR YIELD AND ASSOCIATED TRAITS - N. SAI UDAY YOGITHA; Y. SATISH; Y. PUSHPA RENI; G. VIJAYA KUMAR (The Journal of Research ANGRAU, 2026)
The present study was undertaken during the rabi season of 2024–25 at the RegionalAgricultural Research Station (RARS), Lam, Guntur, Andhra Pradesh, to evaluate the extent ofgenetic variability, heritability and genetic advance in maize (Zea mays L.) inbred lines. A total of50 inbred lines comprising 48 test entries along with two standard checks (LM 13 and LM 14) areassessed using alpha lattice design with two replications. Data was recorded on thirteen quantitativetraits encompassing phenological, morphological and yield-related parameters. Analysis ofvariance revealed highly significant differences among the genotypes for all the traits studiedindicating the presence of considerable genetic variability. The phenotypic coefficient of variation(PCV) exceeded the genotypic coefficient of variation (GCV) for all traits, reflecting the influenceof environmental factors on trait expression. High estimates of GCV and PCV were observed forear height, 100-kernel weight and grain yield per plant suggesting the existence of substantialvariability within the genetic material. Moderate variability was recorded for plant height, earlength and SPAD chlorophyll meter reading, whereas relatively low variability was observed fordays to 50% anthesis, days to 50% silking and days to maturity. High heritability coupled withhigh genetic advance as per cent of mean was recorded for plant height, ear height, number ofkernels per row, 100-kernel weight and grain yield per plant indicating the predominance of additivegene effects and the potential effectiveness of direct selection for these traits. Moderate heritabilitywith moderate genetic advance was observed for ear length, ear girth, number of kernel rows perear and SPAD chlorophyll meter reading, suggesting the involvement of both additive and nonadditivegene actions.